2003
DOI: 10.1021/jm020440w
|View full text |Cite
|
Sign up to set email alerts
|

Distorting Malaria Peptide Backbone Structure to Enable Fitting into MHC Class II Molecules Renders Modified Peptides Immunogenic and Protective

Abstract: The conserved, nonantigenic, nonimmunogenic malaria Merozoite Surface Protein-2 peptide 1, having high affinity for red blood cells, was rendered immunogenic and protective in Aotus monkeys by specifically changing some critical residues. The NMR structure revealed a switch from classical type III' into distorted III' and III beta turns in the protective peptides. These changes may lead to a better fit into the Aotus MHC class II human HLA-DRbeta1 12 molecule equivalent, thus activating the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 21 publications
5
64
0
Order By: Relevance
“…41,44,[50][51][52][53][54][55][56][57][58] This distance was 6.5 ( 0.5 Å and 4.5 ( 1.5 Å shorter in short-lived and long-lasting antibody-inducing but non-protection-inducing modified HABPs, respectively, than in immunogenic, protection-inducing ones; residue orientation was also different. 42,43 In essence, immunogenic protection-inducing modified conserved HABPs have been modified so that they can fit perfectly into the MHC II-peptide-TCR complex for triggering an appropriate immune response, providing tremendous support for using chemically synthesized, specifically modified conserved HABPs in vaccine development.…”
Section: Structural and Binding Characteristics Of Hla-dr Moleculesmentioning
confidence: 90%
“…41,44,[50][51][52][53][54][55][56][57][58] This distance was 6.5 ( 0.5 Å and 4.5 ( 1.5 Å shorter in short-lived and long-lasting antibody-inducing but non-protection-inducing modified HABPs, respectively, than in immunogenic, protection-inducing ones; residue orientation was also different. 42,43 In essence, immunogenic protection-inducing modified conserved HABPs have been modified so that they can fit perfectly into the MHC II-peptide-TCR complex for triggering an appropriate immune response, providing tremendous support for using chemically synthesized, specifically modified conserved HABPs in vaccine development.…”
Section: Structural and Binding Characteristics Of Hla-dr Moleculesmentioning
confidence: 90%
“…When these polymerised conserved HABPs were used for immunisation studies in Aotus monkeys it was found that these native HABP sequences were neither immunogenic nor protection-inducing [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116].…”
Section: Molecular Approach To the Invasion Processmentioning
confidence: 99%
“…However, whereas some HABPs modifications elicited non-protection inducing antibodies in vaccinated Aotus monkeys, [(some induced antibodies having a very short half-life) [119]], other modifications made to HABPs were able to induce high antibody titres against parasite native protein and protected Aotus monkeys from challenge with the highly infective P. falciparum FVO strain [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Although the protection levels achieved by each of these modified HABPs has been limited (Table 1), and individually slightly lower than SPf66, the purpose of our Institute it is to develop a rational methodology for obtaining multi-antigenic, multi-stage, subunit-based synthetic vaccines, malaria being one of them.…”
Section: Molecular Approach To the Invasion Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Such modifications included displacing or shortening native molecule a-helix (Cifuentes et al, 2003b;Cubillos et al, 2003;Espejo et al, 2004;Espejo et al, 2001) or a-helicoid fragment appearing in those native HABPs having a random structure Bermú dez et al, 2005;Bermú dez et al, 2003) or b-turn III distortions (Cifuentes et al, 2003a;Purmova et al, 2002), thus stimulating a considerably improved immune response, increasing antibody titres and inducing protection in some Aotus monkeys against experimental challenge. Table 2 shows Aotus immunisation studies with their respective antibody titres against the parasite (determined by IFA) and their protection capacity regarding experimental challenge.…”
Section: Modified Habpsmentioning
confidence: 99%